BEBERAPA HAL TENTANG HUKUM PIDANA LINGKUNGAN - Supriyanta - - (Joglo, 2006)
ABSTRACTThe environmental law may be enforced by administrative instrument, civilinstrument, and criminal law instrument. All of them are of the same importance.The enforcement of environmental law requires understanding and cooperationbetween the administrative authority, the police and the public prosecutor.Keywords : The environmental law